University Students' Knowledge and Attitudes about Plagiarism: A Web-Based Cross-Sectional Study - Upadhyay, Hari Prasad; Pradhan, Bijay Lal; Sedain, Prativa (BMC Journal of Scientific Research, 2023)
Plagiarism is the act of using someone else's ideas, words, or work without giving them proper credit and presenting it as your own. It is considered a serious ethical and academic offense in most educational institutions and professional settings. The main objective of this research was to find the level of knowledge and attitudes about plagiarism among university level students and various associated factors affecting for level of knowledge and attitudes.An analytical cross-sectional study was conducted among 288 universities level students using non probability sampling. Collected information was checked for completeness and coded with serial number and then analyzed using SPSS-22. Descriptive and inferential statistical tools were used for data analysis. In the descriptive statistics frequency and percentage were calculated for the categorical variable while mean and SD were calculated for continuous variables. In the inferential statistics to find the association between level of knowledge and attitude Chi-Square test were used. p-value